2017
DOI: 10.1088/1361-6528/aa77e3
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of the exchange bias effect in Co/CoO core–shell nanowires

Abstract: We study the magnetic properties of cylindrical ferromagnetic core-antiferromagnetic shell nanowires using Monte Carlo simulations and a classical Heisenberg Hamiltonian in order to elucidate the impact of the oxidized shell on the magnetic properties and the magnetization reversal mechanism. We find that the coupling to the antiferromagnetic shell leads to suppression of the coercivity and emergence of a weak exchange bias effect. Comparison of the magnetization reversal mechanism in the bare and the surface-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
15

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 38 publications
(81 reference statements)
1
16
0
15
Order By: Relevance
“…1 we use dimensionless energy parameters scaled by J F M , which is arbitrarily taken as J F M = 10, and J AF /J F M = -0.5, J int /J F M = -0.5, K F M /J F M = 0.1, K AF /J F M = 1.0 and g = 0.05/J F M . These parameters capture the main features of the Co/CoO exchange coupled system as previous studies of oxide-coated cobalt nanoparticles 14,24 and nanowires 21 have shown. Temperature T and the magnetic field strength H are measured in units of J F M .…”
Section: Model and Simulation Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…1 we use dimensionless energy parameters scaled by J F M , which is arbitrarily taken as J F M = 10, and J AF /J F M = -0.5, J int /J F M = -0.5, K F M /J F M = 0.1, K AF /J F M = 1.0 and g = 0.05/J F M . These parameters capture the main features of the Co/CoO exchange coupled system as previous studies of oxide-coated cobalt nanoparticles 14,24 and nanowires 21 have shown. Temperature T and the magnetic field strength H are measured in units of J F M .…”
Section: Model and Simulation Methodsmentioning
confidence: 70%
“…The third term in Eq. 1 is the Zeeman energy due to the applied field H and the fourth term is the dipolar energy with strength g. For computational efficiency, the dipolar energy term is treated in an embedded cluster approximation with a cluster radius r 0 = 3a 21 .…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…Mag- Table 1. netization reversal in FM nanowires proceeds by nucleation of a pair of domain walls at the free ends of the nanowire, their propagation with opposite velocities and eventually their merge at the center of the wire [6,8,25]. The coupling to an AF shell (S2) modifies the reversal mechanism, as previous experimental [19] and numerical [19,23] works have demonstrated. In an ideal FM/AF nanowire (S2), as it was mentioned above, the unsatisfied bonds at the interface act as nucleation centers of a secondary magnetization reversal mechanism.…”
Section: Magnetization Reversal Mechanismmentioning
confidence: 93%
“…The third term in Eq. 1 is the Zeeman energy due to the applied field along the cylinder axis and the fourth term is the dipolar energy with strength g. For computational efficiency, we decompose the local dipolar field H d−d i ≡ g j D ij · S j into a near-field part that extends up to 3rd nearest neighbor cells and a far-field part that is treated in a mean field approximation [23]. We use micromagnetic parameters typical of cobalt A = 1.3 · 10 −11 J/m, M s = 1.4 · 10 6 A/m, and K u = 3 · 10 5 J/m 3 .…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation